Molecular evidence of genome editing in a mouse model of immunodeficiency - Abdul-Razak, Hayder; Gabriel, Richard; Bartholomä, Cynthia C.; Kalle, Christof von; Schmidt, Michael (Scientific reports, 2018)
Genome editing is the introduction of directed modifications in the genome, a process boosted to therapeutic levels by designer nucleases. Building on the experience of ex vivo gene therapy for severe combined immunodeficiencies, it is likely that genome editing of haematopoietic stem/progenitor cells (HSPC) for correction of inherited blood diseases will be an early clinical application. We show molecular evidence of gene correction in a mouse model of primary immunodeficiency. In vitro experiments in DNA-dependent protein kinase catalytic subunit severe combined immunodeficiency (Prkdc scid) fibroblasts using designed zinc finger nucleases (ZFN) and a repair template demonstrated molecular and functional correction of the defect. Following transplantation of ex vivo gene-edited Prkdc scid HSPC, some of the recipient animals carried the expected genomic signature of ZFN-driven gene correction. In some primary and secondary transplant recipients we detected double-positive CD4/CD8 T-cells in thymus and single-positive T-cells in blood, but no other evidence of immune reconstitution. However, the leakiness of this model is a confounding factor for the interpretation of the possible T-cell reconstitution. Our results provide support for the feasibility of rescuing inherited blood disease by ex vivo genome editing followed by transplantation, and highlight some of the challenges.
Gesehen am 02.04.2019